Possible Effect of Chelation Treatment on Metabolomic and Lipidomic Analysis in Lead Exposure. Issue 5 (1st May 2022) - Çetin, Tugce; Samadi, Afshin; Reçber, Tuba; Dinçer, Asli Karacan; Eser, Burcu; Yalcinkaya, Ahmet; Nemutlu, Emirhan; Öztaş, Yesim; Lay, Incilay; Sabuncuoğlu, Suna
Abstract : This study aimed to evaluate the effectiveness of chelation therapy in Pb exposed workers by determining the changes in the metabolomic profile and to measure and evaluate oxysterol levels resulting from the auto-oxidation of cholesterol. In addition, the levels of sphingosine-1-phosphate (S1P), which is a polar metabolite formed by the metabolism of sphingolipids, was evaluated. This study provides information for lipidomic changes in Pb poisoning patients and shows effectiveness of chelation therapy relative to changes in lipid metabolites. Abstract : Objective: This study aimed to examine patients with lead poisoning in terms of metabolomic profiles and bioactive lipids (oxysterols and sphingosine 1-phosphate [S1P]) before and after chelation therapy. Methods: Consent was obtained from 42 individuals diagnosed with lead poisoning and blood and urine samples were collected before and after chelation therapy. The levels of 7-ketocholesterol (7-KC), cholestan-3b, 5a, 6b-triol (Ctriol), and S1P were measured via LC-MS/MS. Metabolomic analysis was performed via GC—MS. Results: 7-KC and C-triol levels were detected higher before chelation therapy compared with after therapy ( P < 0.001 for both). S1P levels were measured higher before the therapy. The results also showed that sphingolipid metabolism-related pathways were affected by lead toxicity as well as other related pathways. Conclusion: This preliminary study showed that lipid metabolism is affected in lead exposure and chelation therapy is effective in reversing possible damage.